Case Report: Neonatal right atrial mass of uncertain etiology - Svoboda, Libor; Mank, Sabine; Meier, Sabine; Vollroth, Marcel; Kiess, Alexandra; Schürer, Christian (Frontiers in Pediatrics, 2025)
BackgroundNeonatal intracardiac masses are rare and pose significant diagnostic and therapeutic challenges, particularly in differentiating thrombi from tumors.Case summaryWe present the case of a preterm neonate with a right atrial mass of uncertain etiology. Multimodal imaging, including echocardiography and cardiac MRI, suggested the presence of a thrombus—consistent with thrombi being the most common type of intracavitary cardiac mass. As a result, primary anticoagulation therapy was initiated. However, after 16 days without significant change in the mass and given the high risk of embolization and the possibility of a benign tumor, surgical excision was performed. Histopathological analysis of the excised tissue could not definitively distinguish between an organized thrombus and a regressed benign neoplasm, although no malignant cells were identified.ConclusionsThis case highlights the diagnostic uncertainty surrounding neonatal intracardiac masses and the limitations of imaging and pathology in achieving definitive diagnosis. A multidisciplinary approach and long-term follow-up are essential, particularly when the true nature of the mass remains unclear.